Lymphatic platelet thrombosis limits bone repair by precluding lymphatic transporting DAMPs - Yangkang Zheng; Lin Cong; Li Zhao; Pengyu Wang; Lianping Xing; Junling Liu; Hao Xu; Ning Li; Yongjian Zhao; Luying Yuan; Qi Shi; Xueqing Sun; et al. (Nature Communications)
Abstract In the musculoskeletal system, lymphatic vessels (LVs), which are interdigitated with blood vessels, travel and form an extensive transport network. Blood vessels in bone regulate osteogenesis and hematopoiesis, however, whether LVs in bone affect fracture healing is unclear. Here, we investigate the lymphatic draining function at the tibial fracture sites using near-infrared indocyanine green lymphatic imaging (NIR-ICG) and discover that lymphatic drainage insufficiency (LDI) starts on day one and persists for up to two weeks following the fracture in male mice. Sufficient lymphatic drainage facilitates fracture healing in male mice. Furthermore, we identify that lymphatic platelet thrombosis (LPT) blocks the draining lymphoid sinus and LVs, causes LDI, and inhibits fracture healing in male mice, which can be rescued by a blood thinner. Moreover, unblocked lymphatic drainage decreases neutrophils and increases M2-type macrophages of the hematoma niche to support osteoblast (OB) survival and bone marrow-derived mesenchymal stem cell (BMSC) proliferation via transporting damage-associated molecular patterns (DAMPs) in male rats. Lymphatic platelet thrombolysis also benefits senile fracture healing in female mice. These findings demonstrate that LPT limits bone regeneration by impeding lymphatic transporting DAMPs. Together, these findings represent a way forward in the treatment of bone repair.